FACTORS AFFECTING EMPLOYEE RETENTION IN NON-GOVERNMENTAL ORGANIZATIONS IN NAIROBI COUNTY, KENYA. - Njoroge, Samwel Mwangi; Nzulwa, DR. Joyce (Human Resource and Leadership Journal, 2019)
Purpose: To establish the factors affecting employee retention in Non-Governmental Organizations in Nairobi County, Kenya. Methodology: The study embraced descriptive research design in order to provide a framework to examine current conditions, trends and status of events. The study targeted the 47 registered Non-Governmental Organizations in Nairobi County, the target population was all the Executive Directors and the Human Resource directors (total=92). A questionnaire was designed to collect information that contain open ended and closed ended questions. Data was analysed using both descriptive and inferential statistics. This is because descriptive statistics helps to describe the data collected and aim to summarize a sample while inferential statistics are used to interpret the meaning of descriptive statistics besides making propositions about populations and so helps in drawing conclusions. The filled in questionnaires were collected, cleaned, coded and fed in the computer for analysis by SPSS V22 for both descriptive and inferential statistics. Results: The findings of this study suggested that a clear Leadership positively influences the employee retention in NGO's in Kenya. The corresponding change in retention can be explained by a unit change in Leadership clarity with the constant. The research found out that Rewards has a positive influence on employee retention in NGO's in Kenya. The corresponding change in the employee retention in NGO's in Kenya can be explained by a unit change in Rewards. Rewards determine the organizational strategy. Contributions to policy and practice: Expansion of Leadership space to facilitate access by staff and other stakeholders through allocation of more resources towards development. Rewards play a key role in motivating employees, hence retention in the NGO sector in Kenya. The study recommends more policies developed around rewarding of employees.